2021
DOI: 10.1111/bcp.15057
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chemotherapy on the exposure–response relation of abiraterone in metastatic castration‐resistant prostate cancer

Abstract: To assess whether the exposure-response relation for abiraterone is different in prechemotherapy patients compared to post-chemotherapy patients with metastatic castrationresistant prostate cancer (mCRPC). MethodsData were collected from three clinical studies in mCRPC patients treated with abiraterone acetate. Cox regression analysis was used to determine the relation between abiraterone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…With regard to nmCRPC patients, no dose–response data are available; however, it is suggested that there is no exposure–response relationship in this early state of PC at the registered dose. This is in line with the observation that CRPC gets increasingly less sensitive in more advanced stages of disease as has been shown for other ARSIs [ 42 ].…”
Section: Exposure Response Relationshipsupporting
confidence: 90%
“…With regard to nmCRPC patients, no dose–response data are available; however, it is suggested that there is no exposure–response relationship in this early state of PC at the registered dose. This is in line with the observation that CRPC gets increasingly less sensitive in more advanced stages of disease as has been shown for other ARSIs [ 42 ].…”
Section: Exposure Response Relationshipsupporting
confidence: 90%
“…Then, after, Blanchet and coworkers reported on an AA metabolite survey and mentioned that a high metabolic ratio could help to identify patients with increased activity of the main AA metabolizing enzyme and who were at risk for a poorer survival rate [9]. The existence of an exposure threshold of AA concentration linked to survival was also underlined by the data reported by Boerrigter and coworkers [10]. Therefore, it is reasonable to assume that AA PKs may reflect treatment outcome, and this relationship should be strengthened by studies based on a large number of patients.…”
Section: Discussionmentioning
confidence: 98%